APPLIED RESEARCH OF THE RADIAL-RING TYPE OF LEARNING IN THE ACQUISITION OF KNOWLEDGE USING ERGONOMICS - Khaldarov Hikmatulla Akhmatovich (Scholar Express Journal, 2024)
In this article, an attempt is made to study the quality of the learning process of the radial-ring type of the audience in the acquisition of knowledge, using ergonomic modeling.
Keywords: qualities; research; radial-ring; structural